Short Term and Long-Term Efficacy of Calcipotriene/ Betamethasone Dipropionate Foam Combination. - Jalili, Ahmad; Bewley, Anthony; Sticherling, Michael; Gold, Linda Stein (Clinical, Cosmetic and Investigational Dermatology, 2022)
Psoriasis is a well-known chronic disease characterized by the development of erythematous, indurated, scaly, pruritic plaques on the skin with cycles of remission and symptom flare-ups. The management of patients with chronic plaque psoriasis has been more challenging since the Covid-19 pandemic as health care professionals have had to adapt to remote consultations for some patients, and patients have had to adapt to the changing health landscape. The rapid resolution of psoriasis symptoms especially those with a substantial impact on quality of life can improve patient satisfaction and adherence, making it an important factor in successful treatment. Cal/BD foam contributes to improved patient adherence and treatment outcome through its rapid action and superior efficacy versus Cal or BD monotherapy, Cal/BD ointment and gel and clobetasol cream in the short-term flare treatment of psoriasis. Moreover, the benefits of proactive long-term management of psoriasis compared to reactive management and its favourable safety profile are higher efficacy and a better health-related quality of life. Cal/BD foam should be considered an effective topical treatment for short-term flare treatment and long-term control of adult psoriatic patients.
EVALuna2:503674